2017
DOI: 10.1039/c7tc03060f
|View full text |Cite
|
Sign up to set email alerts
|

Past and future of graphene/silicon heterojunction solar cells: a review

Abstract: Graphene/silicon (Gr/Si) Schottky junction solar cells represent an alternative low-cost, easy fabrication structure in photovoltaic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 112 publications
0
33
0
Order By: Relevance
“…On the other hand, active area of Gr–Si solar cells is still limited. Almost all of the Gr–Si solar cells reported have an area smaller than 0.1 cm 2 , which is too small for building photovoltaic modules. As mentioned earlier, a wet transfer method is commonly utilized in the fabrication of Gr–Si solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, active area of Gr–Si solar cells is still limited. Almost all of the Gr–Si solar cells reported have an area smaller than 0.1 cm 2 , which is too small for building photovoltaic modules. As mentioned earlier, a wet transfer method is commonly utilized in the fabrication of Gr–Si solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…2D nanomaterials have been identified as promising materials for future electronics and optoelectronic based devices including solar cells, light‐emitting diodes, transistors, memory devices, photodetectors, laser applications, etc . In particular, 2D material‐based solar cells have gained significant attention because of their easy device fabrication process, excellent optical properties, solution processable approach, low temperature fabrication, and tunable band structure at nanoscale dimensions . For example, 2D graphene with multiple optoelectronic properties such as excellent electrical conductivity and better optical transmittance can be an ideal candidate to combine with Si solar cells.…”
Section: Work Function Of Ti3c2tx Mxene/n+np+‐si Solar Cell (Ev)mentioning
confidence: 99%
“…Inspired by the previous success in carbon nanotube/Si and graphene/Si heterojunction PV cells with high power conversion efficiencies (PCEs), we report a low‐cost, solution‐processable solar cell, based on a Ti 3 C 2 T x ‐on‐Si heterojunction that has initial efficiencies of ≈5% under simulated AM1.5 full solar illumination. We further showed that the PV efficiency of the as‐prepared Ti 3 C 2 T x ‐on‐Si solar cells can be improved to be more than 9% by applying simple chemical treatments using HCl and AuCl 3 .…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the efficiency of charge separation at a solar cell junction formed between the MXene and a semiconductor of a proper bandgap such as silicon (Si) can be improved, in addition to fulfilling the requirements as a transparent conducting electrode. Inspired by the previous success in carbon nanotube/Si [28] and graphene/Si [29] heterojunction PV cells with high power A novel type of solar cell has been developed based on charge separation at the heterojunction formed by a transparent conducting MXene electrode and an n-type silicon (n-Si) wafer. Very recently, Yang et al [27] have demonstrated low-temperature perovskite solar cells with high efficiency and small cell-to-cell variations using solution-processed Ti 3 C 2 /SnO 2 nanocomposites as the electron transporting layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation